STUDY OF REDOX BALANCE OF BLOOD PLASMA AND PERITONEAL FLUID IN WOMEN WITH EXTERNAL GENITAL ENDOMETRIOSIS (World Bulletin of Public Health, 2024)
Endometriosis affects approximately 10% of women of reproductive age worldwide (WHO, 2021), up to 50% of women among them are diagnosed with infertility. Thus, according to WHO estimates, at least 190 million women and adolescent girls around the world currently suffer from this disease at their reproductive age, although some women may suffer after menopause [1, 2, 4, 14]. Endometriosis ranks 2nd in the structure of gynecological morbidity, This, in turn, naturally has a negative impact on the reproductive health of women [1, 3, 6, 9, 10]
Keywords: Endometriosis affects